SURGICAL TREATMENT OF PRIMARY LYMPHEDEMA COMPLICATIONS – A CASE REPORT - Noveski, Lazo; Dzonov, Boro; Mircevska, Elizabeta; Peneva, Margarita; Jovanovska, Katerina (Journal of Morphological Sciences, 2021)
We present a case of a 28-year-old woman with primary lymphedema of the right leg, with tumor formations on her right foot, causing functional disabilities. Tumor formations were removed and histologically confirmed as dermatofibromas. Five years later, the patient was readmitted due to foot problems, keratosis of the heel, as well as increased edema of the dorsum of the foot and lower leg. Liposuction and excision of lymphoedematous tissue from the dorsum of the foot, release of the constrictive band at the level of the anterior surface of the ankle with "Z" plasty, as well as liposuction of lymphoedematous tissue of the lower leg and thigh were performed. The postoperative course was without complications, with a light seroma at the dorsum of the foot. During the 4-year follow-up period, the patient showed a noticeable improvement, with a slow increase in the volume of the lower leg and thigh, which did not reach the preoperative dimensions. Unfortunately, lymphedematous tissue increased again on the dorsum of the foot as prior to surgery. Keywords : lymphedema, tumor, surgery https://doi.org/10.55302/JMS2141126n